Moving towards a transformative diaconia in the Christian Dependency Ministry of the Uniting Reformed Church in Southern Africa : a practical theological approach - Williams, Claudette (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2024.